O pensamento computacional no ensino profissional e tecnol??gico - Geraldes, Wendell Bento (2017)
In Brazil, Professional and Technological Education has received special attention from the State, with the creation of the Federal Institutes of Education, Science and Technology. The introduction of fundamentals of computer science in school curricula in several countries demonstrates the concern of their governments to enable children, youth and adults not only to use these technologies, but to understand how they work with the goal of using this knowledge to address a portion of current problems faced by society. Computation can be seen as the area of knowledge involved with systematic problem solving. Computational Thinking is a problem solving approach based on fundamental concepts of computation and that can be used in several situations to assist in the tasks of everyday life. On this aspect, it is necessary to understand how the abilities related to Computational Thinking can be disseminated in the educational environment by the diverse curricular subjects of the most diverse training courses. This work aims to identify in the pedagogical practices of teachers of professional and technological education what Computational Thinking skills are being developed and which tools serve to support these practices and how they perceive the term. For this, a qualitative analysis of the answers given to an exploratory questionnaire answered by the teaching community of the Federal Institute of Goi??s was carried out. It was verified the inexpressive perception by this community of the meaning of the concept of Computational Thinking, indicating the need for investments The diffusion of this concept and its applicability in academic activities.